2016
DOI: 10.1007/s10068-016-0152-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dipping pretreatment on ochratoxin A accumulation in sultanas and currants

Abstract: The dipping pretreatment on the occurrence of ochratoxin A (OTA) in sultanas and currants was investigated. Grape samples were divided into two groups before a drying process. One group was dipped with potassium carbonate-ethyl oleate, and the other group was left without treatment (the control). OTA were detected using solid-phase extraction clean-up and a high-performance liquid chromatography fluorescence detector. Results showed that OTA content was below the limit of detection in the fresh grapes of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…To enhance the water transport through grape skin and reduce the respective drying time, the chemical pre-treatment of grapes is suggested. On the other hand, the chemical pre-treatment in grapes has been reported to increase the potential hazard of OTA development especially in dried grapes stored unpackaged after drying [19]. The drying temperatures in the present solar drying experiments were lower compared to artificial drying temperatures (>50 • C) normally employed in drying of agricultural products.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…To enhance the water transport through grape skin and reduce the respective drying time, the chemical pre-treatment of grapes is suggested. On the other hand, the chemical pre-treatment in grapes has been reported to increase the potential hazard of OTA development especially in dried grapes stored unpackaged after drying [19]. The drying temperatures in the present solar drying experiments were lower compared to artificial drying temperatures (>50 • C) normally employed in drying of agricultural products.…”
Section: Resultsmentioning
confidence: 60%
“…Some of the previous factors cause localized hardening of the skin, which may increase the susceptibility of the fruit to splitting [14]. Zhang et al [19] investigated the effect of dipping pre-treatment on OTA accumulation in sultanas (white grapes) and currants (red grapes) and concluded that in the untreated samples OTA accumulation was more serious in red grapes than in white grapes, and that in particular this behavior was attributed to the components of red dried grapes that may favor fungal growth, which lead to a faster and higher accumulation of OTA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation